Grupo mediano de personas : Graduación.
Aparece María Eugenia Sibaja Administradora del Centro Universitario San José, Jorge Enrique Guier Esquivel, Ronald García Soto, Francisco Antonio Pacheco Fernández, Enrique Góngora Trejos y Enrique Villalobos Quirós